Concussion and brain health (Position statement 2024) (AIS, 2024)
There has been growing concern in sporting communities in Australia and internationally about the potential health ramifications for athletes from repeated head trauma (RHT) and sport-related concussion (referred to as concussion here on). Concussion affects athletes at all levels of sport, from the part-time recreational athlete to the full-time professional. If managed appropriately, most episodes of concussion resolve over a short period of time, with or without medical intervention. Complications can occur, however, including prolonged duration of symptoms and increased susceptibility to further injury. There is also concern about potential consequences of RHT for long term brain health.